’Favores, Ayuda y Robo’: Views of Continuity in Systemic Change in Rural Nicaragua - Müller, Birgit (Anthropologica, 2022)
While a succession of governments has poured its contrasting ideologies and programs over the rural people in Nicaragua, this article looks at how villagers in Carazo chal? lenged the objectives and categories of the governments of the day in their everyday practices and discourses. Villagers eval? uated official development policies as they were applied locally, in their own terms of favores (in the sense of favours), ayuda (in the sense of help but also in the material sense of gift) and robo (in the sense of theft, but also fraud and deception). With these three terms they appraised relationships of power and control with agents of the government and of NGOs with the same moral frames with which they assessed other more direct personal relationships of reciprocity, dependency and exploitation. They thus gave their own reading of the challenges in their daily lives brought about by systemic transformations and questioned the promises of a better life.